Interest in Science and Scientific Habits of Mind of High School Students in West Kalimantan Province - Ahsani, Mar’atuzzakiya; Prodjosantoso, Anti Kolonial (Jurnal Pendidikan MIPA, 2024)
This study investigates the interest in science and scientific habits of mind among high school students in West Kalimantan Province. It examines the relationship between these two factors and explores differences based on gender and school status. The study used a survey method, involving 38 schools from six districts selected through a two-stage cluster random sampling technique. Data were collected via questionnaires with 22 statements on interest in science and 32 on scientific habits of mind. Results indicated that both male and female students showed good levels of interest in science, with private school students displaying higher interest than public school students. Similarly, scientific habits of mind were higher among private school students. A moderate relationship between interest in science and scientific habits of mind was found. Male students showed a significantly higher interest in science, but no significant gender difference in scientific habits of mind, though males scored slightly higher on average. Significant differences were also found when comparing interest in science and scientific habits of mind simultaneously between genders and school statuses, with males and private school students outperforming their counterparts.       Keywords: gender, interest in science, school status, scientific habits of mind. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp765-783